An experimental study on influence of plate size on actual and perceived energy intake among undergraduates in a public university, Malaysia - Shalihin, Siti Amirah Shaheera; Jamaluddin, Rosita; Cheah, Khang Jin; Mohamad, Najihah (Medknow Publications, 2021)
Aim: A within-subjects experimental study design was conducted to determine the influence of plate sizes on the actual compared to the perceived energy consumed. Method: Fifty-eight participants (45 female, 13 male) were selected from a faculty in a public university. On separate experimental days, they were invited to a lunch buffet dishes in which white rice, a chicken dish and stir-fried vegetables were self-served using small (7-inch/18cm) and large (9-inch/23cm) diameter plates. Anthropometric measurements, perceived energy intake, actual energy intake and socio-demographic information were collected. The weight of each food was used to calculate the actual energy consumed. Results: On the 7-inch/18cm plate size, the perceived dietary intake was significantly higher than the actual dietary intake (p<0.01). While on the 9-inch/23cm plate size, participants perceived a significantly lower dietary intake compared to the actual dietary intake (p<0.01). There was a significant difference in actual and perceived dietary intake between the 2 plate sizes (p<0.001). Conclusion: Participants underestimated their dietary intake on a large plate and overestimated their dietary intake on a small plate. It can be concluded that plate size has an influence on dietary intake and could be considered as part of weight loss interventions.